A Takagi-Sugeno Fuzzy Model for Greenhouse Climate - Haj Hamad, I.; Chouchaine, A.; Bouzaouache, H. (Engineering, Technology & Applied Science Research, 2021)
This paper investigates the identification and modeling of a greenhouse’s climate using real climate data from a greenhouse installed in the LAPER laboratory in Tunisia. The objective of this paper is to propose a solution to the problem of nonlinear time-variant inputs and outputs of greenhouse internal climate. Combining fuzzy logic technique with Least Mean Squares (LMS), a robust greenhouse climate model for internal temperature prediction is proposed. The simulation results demonstrate the effectiveness of the identification approach and the power of the implemented Takagi-Sugeno Fuzzy model-based algorithm.